Effects of speaker authority level on the maintenance of discrepant rule following by children (Brazilian Journal of Behavioral and Cognitive Therapy, 2024)
This study investigated the effects of the speaker's authority level on the maintenance of discrepant rule-following by children. Twelve children were exposed to a computerized matching to sample task, programmed with five blocks of 20 trials each. In blocks 1, 3, and 5, a rule corresponding to the contingencies was presented by the computer. In blocks 2 and 4, a rule that differed from the contingencies was presented by speakers with different levels of authority (adult teacher and child). Half of the participants were first exposed to the presentation of the discrepant rule by the adult teacher and then by the child. The other half was exposed to the opposite order. All participants abandoned following the discrepant rule and no significant difference was observed between levels of authority. It was confirmed that following the rule tends to be abandoned when there is a discrepancy between the rule and the contingency in force.
Keywords: authority; rule-governed behavior; behavioral flexibility; rules